Motivation of sports achievement Field study in clubs for the disabled in Baghdad Disability, achievement, sport, self (Journal of the College of Basic Education, 2022)
The research deals with an important topic, which is the motive for sporting achievement among an important segment of society, but the illusion of the handicapped, and achievement is one of the basic axes of the concept of mental health, where it can be observed directly within the observed behavior, and that the motivations for the achievement lie in the culture, family and individual personality, there are some cultures that encourage its members On achievement and creativity while other cultures cease to do so. The research dealt with these concepts on several axes, the first component included the elements of the research from a problem, importance and goals. As for the second axis, it dealt with presentation and interpretation of the most important previous studies and the third came to include the concepts of research and from it Lete research chapter is devoted to the analysis of the fourth Alastpianih .information gathered by the researchers